Building healthy societies: A framework for integrating health and health promotion into education - Thompson,D; Leis,M; Davies,N; Viner,R (The World Innovation Summit for Health (WISH), 2020)
The report explores how health activities can be implemented into education systems to deliver improved health outcomes.